Fat‐Finger Trade and Market Quality: The First Evidence From China. Issue 10 (4th February 2016) - Gao, Ming; Liu, Yu‐Jane; Wu, Weili
Abstract : More trading is algorithmic or computer generated, and in markets where it is allowed, high frequency. However, what happens when there is an algorithmic trading error? This study attempts to answer that question by examining the August 16, 2013, fat‐finger trade in Chinese equity and equity futures markets. We find that both markets were excessively volatile, illiquid, and positively skewed. Moreover, we document that index returns are predictable for a short time, indicating that the fat‐finger event induced an inefficient market. Our results highlight the importance of market surveillance and regulation to lessen the damage of future fat‐finger events. © 2016 Wiley Periodicals, Inc. Jrl Fut Mark 36:1014–1025, 2016